Bacteriological Study of the Bacteria Cause Urinary Tract Infection of Patients Admitted to Cardiac Care Unite a Baqubah General Teaching Hospital - Najim, Hanan Thamer; Farhan, Abbas Abod; Athab, Ahmed Methab (Diyala Journal of Medicine, 2018)
Background:Urinary tract infection patient Urinary Tract Infection ( UTI ) one of commonest types of patient admitted to CCU ( cardiac care unit ) of other medical wards this is occur directly from contact to infected hand or material or during catheterization. Objective:To evaluation common bacterial cause UTI in patients admitted Cardiac Care Unite to show the antimicrobial agent and bacteria resistant and production the biofilm. Patients and Methods: Collection of samples from urine aseptically for culture.Isolation and identification of uropathogens using biochemical tests and testing ability of these bacterial isolation for virulence production and testing the antimicrobial susceptibility test. Results: It is A total of 135 catheter samples were collected from patient (135) catheter samples from patients in CCU at Baqubah General Teaching Hospital for the period from 1st November 2016 to 1st March 2017 frommales and female, and the samples and cultured on the medium blood agar and MacConkey agar. Then growing bacterial farms subjected to microscopic and biochemical tests for the diagnosis of bacteria. Escherichia coli with a ratio 31.8% , and (20)isolations of Proteus mirabilis with a ratio 18.2%, 16 isolates of Klebsiella pneumonia, (14) isolations of Pseudomonas aeruginosa with a ratio 12.7% .The Antimicrobial sensitivity is investigated for (9) antibiotics from different groups including; The results show a high resistance to most of the antibiotics under study, and resistance all isolates ware of Aztreonam ,Cefotaxime , Co-Trimoxazol with ratio 95% , Naldixic acid with ratio 100%, Tetracycline 75% , Gentamycin 70% and Antimicrobial sensitivity to antibiotics to Amikacin 45% followed by Ciproflaxcin 50% and tobramycin 80% . All kinds of bacteria were produced in biofilm in the ELISA method with a ratio 100% ,while Congo red with a ratio 50%. Conclusion: It was observed that multiple antibiotic resistance was common among local isolates of the bacteria under study and Biofilms are important in protecting the bacteria inside the catheter from antibiotics. Key words:Gram Negative bacteria, Antibiotics ,Biofilm ,Urinary Tract Infection , cardiac care unit.